Application of Safranine O Optical Detector in Environmental and Food Analysis - Kazemzadeh, A.; Amin, M.H. (Asian Journal of Chemistry, 2010)
The work presented here describes the oxalic acid detector was developed by immobilizing a direct indicator dye in an optical detecting film for food and environmental monitoring. This detector was fabricated by binding sarfranine O to a cellulose acetate film that had previously been subjected to an exhaustive base hydrolysis. The membrane has good durability (> 8 months) and a short response time (< 10 s). Oxalic acid can be determined for the range 0.15- 6.50 μg mL-1 with 3σ detection limits of 60 ng mL-1. The method is easy to perform and uses acetylcellulose as a carrier. The reagents used for activating the cellulose support are inexpensive, non-toxic and widely available.